Self-learning skills perceveid in communities of inquiry of portuguese higher education students - Moreira, J. António (2014)
The purpose of this study was to report evidence obtained in Communities of Inquiry (CoI) as framed by the work of Garrison, Anderson and Archer (2000) that was carried out in different groups, and identify the emergent learning skills of its students. The study comprised 510 undergraduate students enrolled in blended online courses offered through Moodle platform during one semester. It considered students from different Portuguese schools, of University and Polytechnic in Health, Education and Psychology Courses. Moreira and Almeida (2011) have suggested that CoI framework is a valid, reliable, and efficient measure of its dimensions within the Portuguese population. Assuming the CoI survey as a useful evaluation tool for providing feedback about the effectiveness of online courses in the construction of effective learning communities, we’ve studied the skills students recognize they acquire in virtual environments of learning, using the adapted Self-Learning Competence Scale (Lima-Santos, Rurato, & Faria, 2000). We’ve con- cluded that in both institutions, University and Polytechnic, relevant learning experiences have been fos- tered, towards the emergence of communities of inquiry, in which the students perceived that they have developed self-learning competences.